Comparison Analysis of Unit Prices for Reinforced Concrete Column Work using the 2022 Indonesian National Standard (Sni) Method and Field Data (An Empirical Study On the Construction Project of the National Land Agency Building in Banjarbaru) - Hendra, Cahyadi; Gusti, Maysarah; Abdurrahman, . (INTI International University, 2024)
In construction management, there are various stages of problems in terms of managing the project budget, so it is necessary to have a design or estimation of the project budget by analyzing construction costs. Currently, service providers tend not to fully calculate unit price analysis based on SNI analysis but rather on their own analysis or previous experience in completing construction work. Based on this, it is necessary to compare unit price analysis between the SNI method and field data. This study aims to determine the unit prices in the field and compare the price differences between the SNI 2022 method and field data in the National Land Agency Building Construction Project in Banjarbaru. The results of this analysis show that the price based on SNI 2022 analysis is Rp368,900,072.55, while the price based on field observations is IDR 269,231,757.50. Based on the analysis results of both methods, the cost difference between the SNI 2022 analysis and the actual field conditions for the National Land Agency Building Construction Project in Banjarbaru is IDR 99,668,315.02.